تأثير العلاج بالمساج وتقنيات التنفس على الألم الشديد عند المرأة أثناء المخاض - دونا, عيسى; صواف, عامر (Latakia University Journal -Medical Sciences Series, 2018)
تُعتبر الولادة الطبيعية تجربة مميزة في حياة الأم, لكنها تترافق بحدوث الألم الشديد نتيجة تقلصات الرحم خلال المخاض لذلك فإن التحكُّم و السَّيطرة على هذا الألم الشديد يعتبر مطلباً هاماً لهن, ويعتبر المساج وتقنيات التنفس خلال المخاض من الطرق اللادوائية التي يمكن أن تساعد الأمهات على تحمل ذلك الألم, لذلك هدفت هذه الدراسة شبه التجريبية إلى معرفة تأثير العلاج بالمساج وتقنيات التنفس على الألم الشديد عند 30 امرأه أثناء المرحلة الأولى من المخاض تم اختيارهن بطريقة العينة الملائمة من مشفى التوليد والأطفال ومشفى تشرين الجامعي في محافظة اللاذقية, حيث قسمن عشوائياً إلى ثلاث مجموعات: (10) خضعن للعلاج بالمساج, و(10) خضعن للعلاج بتقنيات التنفس (10) خضعن للعلاج بالمساج وتقنيات التنفس معاً, واستخدم الباحث أدوات لجمع البيانات الديموغرافية وقياس شدة الألم وفق ما تحدده السيدة لفظياً و شدة الألم وفق ما يبدو على وجه السيدة. وتوصلت الدراسة إلى حدوث انخفاض في شدة الألم عند السيدات في العينة عند تطبيق كل من المساج وتقنيات التنفس على حدى وعند تطبيقهما معاً أثناء المرحلة الأولى من المخاض. وأوصت الدراسة الحالية بإجراء المساج وتقنيات التنفس خلال المرحلة الأولى من المخاض للتخفيف من ألم المخاض, وتثقيف القابلات حول أهمية المساج و تقنيات التنفس في التخفيف من آلام المخاض وتدريبهن على تطبيقها, وإجراء أبحاث حول فعالية المشاركة بين استخدام باقي طرق تخفيف الألم غير الدوائية وبين عدم المشاركة بينها. Natural birth is a unique experience in the mother's life, but it is associated with severe pain due to uterine contractions during labor, so the control of this pain is an important requirement for them. The massage and breathing techniques during labor are considered Non-pharmacological methods that can help mothers cope with this Pain, for that reason this semi-experimental study aimed to know the effect of massage therapy and breathing techniques on severe pain in (30) women during the first stage of labor chosen by in the obstetrics and children's hospital and university Tishreen Hospital in Lattakia, where they randomly assigned to three groups: (10) were treated with massage therapy, (10) were treated with breathing techniques, and (10) were treated with massage and breathing techniques together. The researcher used tools to collect demographic data and to measure the pain intensity as determined by the women verbally, and the intensity of the pain as it appears on the face of the women. The study found a decrease in the intensity of pain in the women in the sample when applying both massage and breathing techniques on their own and when applied together during the first stage of labor. The current study recommended massage and breathing techniques during the first stage of labor to reduce labor pain, educate midwives on the importance of massage and breathing techniques in the alleviation of labor pains and train them to apply it, and to conduct research on the effectiveness of participation between the use of other methods of non-pharmacological pain relief and non-participation Among them.